Can confidence indicators be useful to predict short term real GDP growth? - Annabelle Mourougane; Moreno Roma (European Central Bank (ECB), 2002)
We investigate the usefulness of the European Commission confidence indicators in forecasting real GDP growth rates in the short-run in selected euro area countries (Belgium, Spain, Germany, France, Italy and the Netherlands) which account for almost 90% of the euro area. We estimate a linear relationship between real GDP and confidence indicators and we compare the forecasting performance of the estimated models with a benchmark ARIMA model. We generally find that confidence indicators can be useful in forecasting real GDP growth rates in the short run in a number of countries (Belgium, Germany, France, Italy and the Netherlands). Notwithstanding some signs of instability in the relationship between confidence indicators and real GDP, improvements with the use of time-varying parameter models appear to be fairly limited but confirm the findings obtained with constant parameter techniques. The results are robust to a wide range of variant tests implemented.
Keywords: C22; E27; 330